The potential of hybrid antibodies secreted by hybrid-hybridomas in tumour therapy. - Clark, M; Gilliland, L; Waldmann, H (1988)
Using a simple method for the selection of hybrid cell growth from the cell fusion of pairs of existing hybridoma cell lines, 2 different hybrid-hybridoma cell lines were produced. Both hybrid-hybridomas secreted bi-specific antibody with similar specificity for human CD3 and for mouse Thy-l but in one case the parental antibody isotypes were both IgG2b and in the other case the CD3 antibody was IgG2b and the anti-Thy-l antibody was IgG2c. In a model in vitro system both bi-specific antibodies were able to elicit potent cell killing of a Thy-l expressing mouse tumour cell line by human effector cell blasts. The cell blasts were generated from resting peripheral blood mononuclear cells using a mitogenic monoclonal antibody (MAb) (YTH361). The parental anti-Thy-l IgG2b but not the IgG2c antibody was also able to mediate cell killing by ADCC. This ADCC killing was inhibited by a MAb to the CD16 Fc receptor but the killing elicited by the bi-specific antibodies was not. Both mechanisms of tumour cell killing may be of great potential in human tumour therapy with MAbs.